A CULTURA DO GIRASSOL NO URUGUAI E NA ARGENTINA (DE UM RELATÃ“RIO DE VIAGEM) - Mendes, Pedro Teixeira (REVISTA DE AGRICULTURA, 2016)
A CULTURA DO GIRASSOL NO URUGUAI E NA ARGENTINA (DE UM RELATÃ“RIO DE VIAGEM)